The cheese trap : how breaking a surprising addiction will help you lose weight, gain energy, and get healthy - Barnard, Neal D., 1953-; Burton, Dreena, 1970- (Grand Central Life & Style, 2017)
Cites the health-compromising qualities of cheese and its immoderate consumption, outlining a radical program for losing weight, improving overall health, and managing cheese cravings.